INZ-701, a recombinant ENPP1-Fc protein, effectively treats and prevents neointimal proliferation in WT and ENPP1 Deficient mice. (10th June 2022) - Rutsch, F; O'brien, K; Nitschke, Y; Sullivan, C; Howe, J; Lynch, A; Schrier, D; Thompson, D; Sabbagh, Y
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Inozyme Pharma Inactivating mutations in ENPP1, which encodes the ecto-nucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1), underlie the rare inherited disorder, generalized arterial calcification of infancy (GACI)/autosomal recessive hypophosphatemic rickets type 2 (ARHR2) also known as ENPP1 Deficiency. ENPP1 Deficiency is characterized by calcification of large and medium sized arteries and marked neointimal proliferation of arteries, leading to arterial stenosis and severe cardiovascular and skeletal complications. ENPP1 Deficiency is associated with a 50% mortality rate in the first six months of life, and there are no approved treatments. Previous research demonstrated that INZ-701 protein prevented arterial calcification in an ENPP1 deficient mouse model (Enpp1 asj/asj). This study was designed to determine whether INZ-701 can prevent neointimal proliferation in WT and an ENPP1 deficient mouse model (ttw/ttw). Carotid ligation was performed to induce intimal proliferation in the mice. In the preventive arm of the study, INZ-701 (10mg/kg) or vehicle was administered subcutaneously every other day starting in 6-week-old ttw/ttw-mice. Carotid ligation was performed in these mice at the age of 7 weeks and dosing continued for another 2 weeks. Carotid intimal and medial area caudal from the ligation were analyzed by histomorphometry 14 days and 21 days after carotid ligation. In the therapeutic arm of the study, INZ-701 (10 mg/kg) or vehicle was administered subcutaneously every other day starting 7 days after carotid ligation, when intimal proliferation had already developed, in 8-week-old ttw/ttw-mice. After one week of treatment, histomorphometry was performed. Fourteen days after carotid ligation, ttw/ttw-mice preventatively treated with INZ-701 showed a significantly reduced intimal area (p<0.001) and intimal/medial (I/M) ratio (p<0.001) compared to those treated with vehicle. This effect was also observed in mice treated with INZ-701, which were treated for 28 days and were subsequently dissected 21 days after carotid ligation. Interestingly, similar effects of INZ-701 were found in WT mice in the preventative study. In the therapeutic arm of the study, subcutaneous injection of INZ-701 beginning at 7 days post carotid ligation also led to a significant reduction in the I/M ratio (p<0.001) in the INZ-701 treated group compared to vehicle treated ttw/ttw-mice. These findings demonstrate that INZ-701 prevents neointimal proliferation after carotid injury in a murine model of ENPP1 Deficiency. INZ-701 is hypothesized to restore circulating levels of AMP and adenosine, both potent inhibitors of intimal hyperplasia. Neointimal proliferation is a key feature in the pathophysiology of ENPP1 Deficiency and our results build on prior evidence to support the potential of INZ-701 to treat this rare and life-threatening disease.